SOCIETY-BASED ENGLISH COMMUNITY (SOBAT): EFL LEARNERS’ STRATEGY IN LEARNING AND PRACTICING ENGLISH OUTSIDE THE WALLS - Bahar, Andi Kaharuddin; Latif, Ismail (Universitas Hasanuddin, 2019)
As for most Indonesian learners of English, classroom is the only place to learn and to practice English either with classmates or teachers. However, they do not to have plenty of opportunities to practice in English when they leave the classrooms. This has encouraged many of the learners seek strategies that allow them to learn and to use English outside the walls of the classrooms. This paper aims to introduce an approach which can be used as an English learning strategy for EFL learners that they can learn and practice English outside the classroom. This approach is hereinafter referred to as the Society-Based English Community (SOBAT). Therefore, the discussion of this paper focuses on three main points. First, it presents a theoretical discussion on the SOBAT concept. Second, it introduces procedures that can be used by EFL learners to establish SOBAT. Third, it outlines several proposed activities that can be carried out in this community. Forming this community is believed to be able to provide four main benefits: providing the EFL learners with plenty of opportunities not only to learn but also to practice English collectively, forming a habit of using English as intensive as possible for the sake of establishing a community of English whose members actively communicate in English and use English the first lingua franca, giving the members a chance to become interactive, creative, active and effective EFL learners, developing their assertiveness, critical thinking, leadership, initiative as well as inclusiveness by taking a part in discussions and debates on important issues of this country.